О непрерывном культивировании трихомонад - Падченко, И.К. (Вестник зоологии, 1975)
The designed peculiar device permits a continuous cultivation of Trichomonadidae to be provided under conditions of any laboratory. The process of the continuous cultivation in the device takes place without subculturing and replacing the nutrient medium for above 8 months. The device is made as a rectangular tank divided into raws of cells connected as communicating vessels. It is established that the cultivated strains of Pro- tozoa in the process of continuous cultivation do not change their most important biological properties: morphological characters, stability, chemiosensitivity, biochemical activity and other properties typical of this species.